Educational Intervention on Risk Factors Associated with Malocclusions in Five-year-old Children - Amarelys Morera Pérez; Nora Sexto Delgado; Boris Yanes Tarancón; Anabel Casanova Lezcano (Medisur)
Background: educational programs aimed at increasing knowledge on oral health and promoting proper oral hygiene habits allow controlling or limiting the development of dento-maxillofacial defects that lead to many aesthetic, functional and mental disorders. Objective: to assess the effectiveness of an educational intervention on risk factors associated with malocclusions in children aged five years. Methods: a quasi-experimental, before and after study was conducted in 67 children living in the Health Area number 2 in Cienfuegos municipality. Risk factors associated with malocclusions were identified, as well as the knowledge needs of the children and their parents. An educational program on risk factors associated with malocclusions was designed and implemented. Surveys were applied before and after the intervention. The variables studied included risk factors associated with malocclusions and the level of knowledge about them. Results: children and parents increased their knowledge about risk factors associated with malocclusions. Ninety four point three percent of the most common oral habits (tongue thrusting, finger-sucking and bottle feeding) were eliminated. Conclusion: the intervention was effective since it raised the level of knowledge of the children and their parents and led to the elimination of a considerable number of modifiable risk factors associated with malocclusions.